Serum ferritin and HCV infection in Nigerian patients with primary liver cell carcinoma (2006)
A prospective study aimed at determining the relationship between hepatitis C virus (HCV) infection and serum ferritin in Nigerian patients with primary liver cell carcinoma(PLCC) was carried out at the University College Hospital (UCH), Ibadan; Nigeria, The study invovled 42 adult Nigerians maade up of 14 healthy subjects as controls and 14 patients each PLCC and liver cirrhosis(LC) who consented to participate in the study. The subjects were controlled for age and sex. The diagonosis of the disease was made from relevant clinical features, utlrasonography and histology of liver biopsy specimen. Blood specimen collected from the subject were analysed for ferritin by radio-immuno assay using Amersham Kits, hepatitis B virus (HBV) infection using HBsAg dtection and anti-HCV by ELISA (Sanofi Pasteur France). The study protocol was approved by the Joint UI/UCH Ethical Review Board. data obtained was analysed with the SSPS software at a level of significance of p<0.05. Serum ferritin> 700ng/ml was detected only in 50% and 14% of the patients with PLCC and LC respectively with specificity of 93% as well as negative (78%) and postive (79%) predictive value, Serum anti-HCV and HBsAg were present in 14% and 71% of patients with PLCC respectively (p<0.005). Similarly, 29% and 14% of the patients and the controls respectively were sero-positive for anti HCV while serum HBsAg was detected in equal proportions of the patients with LC(50%) and the controls (43%(43%). There was correlation elevated serum ferritin and HBsAg (X2 with yates correction=5.04, p=0.025) but none with serum anti-HCV. In conclusion, the study shows that serum ferritin level > 700ng/ml is indicative of PLCC among Nigerians especially in the presence of HBV infection but may not be useful when there is assocaited HCV infection.